Economic anxieties, fear of crime, and punitive attitudes in Latin America. (April 2020) - Singer, Alexa J; Chouhy, Cecilia; Lehmann, Peter S; Stevens, Jessica N; Gertz, Marc
Using data from the 2012 AmericasBarometer survey collected in nine Latin American countries ( n = 14, 705), this study examines two theoretically relevant potential sources of punitiveness: economic anxiety and fear of crime. Focusing on these two sources, we explore whether the public opinion dynamics often highlighted by punitiveness scholars also apply to the Latin American context and can thus be of value to explain recent movements towards punitive policies in that region. Generalized Structural Equation Modeling (GSEM) and bootstrapping are used to assess the direct effects of perceived national and personal economic insecurity on punitive sentiments as well as the indirect effects of these attitudes on punitiveness through fear of crime during a time of reduced economic growth, increased economic inequality, and harsh criminal justice policies. Results show that economic anxieties are positively associated with fear of crime, though their effects on support for increased punishments are mixed. Additionally, the effects of economic insecurity on punitiveness are partially mediated by fear of crime, supporting theoretical notions that insecurity produces fear of crime and subsequently influences punitiveness.